Cell cycle regulation of the T-box transcription factor tbx2. - Bilican, B; Goding, C (2006)
T-box transcription factors play key roles in development and in particular the determination or maintenance of cell fate. Tbx2 is a transcriptional repressor implicated in several developmental processes and which has also been implicated in cancer through its ability to suppress senescence via repression of the p19(ARF) and p21(Cip1) (CDKN1A) promoters. However, despite its importance, little is known about how Tbx2 may be regulated. Here, we show that Tbx2 protein expression is tightly regulated during cell cycle progression, with levels being low in G1, increasing in mid-S-phase and persisting at high levels though G2 until finally undergoing a dramatic reduction at the onset of mitosis. Moreover, in S-phase, Tbx2 is present at a subset of late, but not early, replication foci and a significant fraction of Tbx2 is tightly associated with the nucleus in small DNA-associated foci that do not correspond with telomeres, PML or cajal bodies. The results are consistent with Tbx2 playing a role in cell cycle progression and organization of subnuclear compartments.